Lipoprotein(a) as a risk factor for atherosclerotic cardiovascular disease in patients in non-metropolitan areas of Brandenburg, Germany - Hillmeister, Philipp; Li, Kangbo; Dai, Mengjun; Sacirovic, Mesud; Pagonas, Nikolaos; Ritter, Oliver; Bramlage, Peter; Bondke Persson, Anja; Buschmann, Ivo; Zemmrich, Claudia (Frontiers in Cardiovascular Medicine, 2024)
In the non-metropolitan region of Brandenburg (Germany), which is characterized by high rates of cardiovascular diseases and underserved medical care, there is a lack of awareness of Lp(a) as a risk factor. Additionally, data from patients with atherosclerotic cardiovascular disease in diverse regional backgrounds, including the understudied Brandenburg cohort, and varied health care statuses remain insufficient.In this WalkByLab study, Lp(a) was monitored in a Brandenburg, Germany nonmetropolitan cohort (n = 850) of 533 patients at high cardiovascular risk and 317 healthy controls. Patients underwent a comprehensive angiological screening. Blood serum analysis, medical and family history, cardiovascular risk and disease status, life style and quality of life were investigated. All parameters were evaluated with regard to a low and high Lp(a) group (<>50 mg/dL).Results: Brandenburg patients with cardiovascular diseases showed higher-Lp(a) levels as compared to healthy controls (24.2% vs 14.8 %, p = 0.001), and the high-Lp(a) group demonstrated a higher prevalence of coronary, peripheral, or cerebrovascular diseases than the low-Lp(a) group (p = 0.004). In a logistic regression with different characteristics, Lp(a) was an independent risk factor significantly associated with ASCVD (OR 2.26, 95% CI 1.32-3.95, p=0.003). The high-Lp(a) group showed a higher proportion of patients with coronary, peripheral or cerebrovascular disease compared to the low-Lp(a) group (50% vs. 36.8%; 57.7% vs. 45.8%; 17.6% vs. 9.2%; p = 0.004), heart failure (72.8% vs. 53.2%, p = 0.014), myocardial infarction (24.7% vs. 13.9%, p = 0.001). The high-Lp(a) group had higher rates of statin (63.1% vs. 50.4%, P = 0.003), Ezetimibe (14.8% vs 5.5.%, p = 0.001) and beta blocker (55.7% vs 40.7%, p = 0.001) treatments. Lp(a) levels are independent of physical activity or smoking behavior and do not change over time (12M).Our study highlights the elevated Lp(a) levels in Brandenburg cardiovascular patients and identifies them as an independent risk factor for ASCVD, which has implications for the cardiovascular health of the non-metropolitan population.